The VAChT(Y49N) mutation provides insecticide-resistance but perturbs evoked cholinergic neurotransmission in Drosophila - Vernon, Samuel W. (PLoS One, 2018)
Global agriculture and the control of insect disease vectors have developed with a heavy reliance on insecticides. The increasing incidence of resistance, for virtually all insecticides, threatens both food supply and effective control of insect borne disease. CASPP ((5-chloro-1’-[(E)-3-(4-chlorophenyl)allyl]spiro[indoline-3,4’-piperidine]-1-yl}-(2-chloro-4-pyridyl)methanone)) compounds are a potential new class of neuroactive insecticide specifically targeting the Vesicular Acetylcholine Transporter (VAChT). Resistance to CASPP, under laboratory conditions, has been reported following either up-regulation of wildtype VAChT expression or the presence of a specific point mutation (VAChT(Y49N)). However, the underlying mechanism of CASPP-resistance, together with the consequence to insect viability of achieving resistance, is unknown. In this study, we use electrophysiological characterisation of cholinergic release at Drosophila larval interneuron→motoneuron synapses to investigate the physiological implications of these two identified modes of CASPP resistance. We show that both VAChT up-regulation or the expression of VAChT(Y49N) increases miniature (mini) release frequency. Mini frequency appears deterministic of CASPP activity. However, maintenance of SV release is not indicative of resistance in all cases. This is evidenced through expression of syntaxin or complexin mutants (sytx(3-61)/cpx(SH1)) that show similarly high mini release frequency but are not resistant to CASPP. The VAChT(Y49N) mutation additionally disrupts action potential-evoked cholinergic release and fictive locomotor patterning through depletion of releasable synaptic vesicles. This observation suggests a functional trade-off for this point mutation, which is not seen when wildtype VAChT is up-regulated.